(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
MANET is a self-configuring network of wireless mobile nodes. Since the nodes in a MANETrun on batteries, power is a precious commodity. Both the routing technique mobility model are crucialto MANET performance. A node’s mobility, as represented by a mobility model, is a significant factor toconsider when assessing an effectiveness of routing protocol. For MANETs to function, it is essentialthat energy consumption be restricted. The focus of this investigation is on how different mobilitymodels effect the amount of energy consumption by different MANET routing methods. Using NS2, wesimulate the energy consumption of various mobility models to compare their relative efficiency.